Adress to the anthropological section - (:unkn) unknown (My University, 1905)
There are various ways in which man can study himself, and it is clearly impossible for me to attempt to give an exposition of all the aims and methodsof the anthropological sciences ; I propose, therefore, to limit myself to a general view of South African ethnology, incidentally referring to a few of the problems that strike a European observer as needing further elucidation. It seems somewhat presumptuous in one who is now for the first time visiting this continent to venture to address a South African audience on local ethnology, but I share this disability with pratically all students of anthropology at home, and my excuse lies in the desire that I may be able to point out to you some of the directions in which the information of anthropologists is deficient, with the hope that this may be remedied in the immediate future.ay in and some ways out of totemism...
Keywords: African Research